A THEMATIC LITERATURE REVIEW ON SUSTAINABLE SUPPLY CHAINS IN FMCG AND THE WAY IT IMPACTS ORGANISATIONAL SUSTAINABILTY - Jadhav, Swapnali Prakash; Ubale, Satish; Ubale, Deepali Satish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The FMCG sector within the Indian economy is regarded as the fourth largest in terms of its magnitude. It stands as a crucial catalyst driving the Indian economy forward. Occupying the fourth position in the Indian economy, this sector caters to nearly three million individuals nationwide. These products are prevalent among individuals of all social classes, irrespective of their age, socioeconomic status, or social standing. Comprising food and beverages, personal care products, and household items, these three primary segments collectively represent 19%, 31%, and 50% of the total industry. The FMCG sector in India derives over 40% of its revenue from semi-urban and rural regions, with a significant impact. In the context of Indian economy, the Fast-Moving Consumer Goods (FMCG) industry holds a significant position, necessitating an adoption of sustainable practices. Incorporation of sustainability in FMCG sector not only tackles environmental issues but also presents possibilities for enduring economic and social advantages. This Literature review-based research paper investigation concentrates on examining the sustainable supply chain practices in Fast-Moving Consumer Goods that is FMCG sector in India. The systematic investigation talks about potential areas for enhancing sustainable supply chain management within the Indian FMCG industry and anticipates the future integration of sustainability initiatives.